Fixed and dilated pupils after trauma, stroke, and previous intracranial surgery: management and outcome. Issue 2 (1st August 2001) - Clusmann, H; Schaller, C; Schramm, J
Abstract : OBJECTIVES: To clarify whether different causative events (trauma, stroke, intracranial surgery), time of intervention, and treatment mode influence outcome, patients with fixed and dilated pupils (FDPs) in a prospective neurosurgical series were evaluated. METHODS: Ninety nine consecutive patients who presented with or developed one or two FDPs, were split into three groups according to the respective aetiology: 46 patients had a trauma, 41 patients a stroke (subarachnoid or intracerebral haemorrhage), and 12 patients had undergone previous elective intracranial surgery. Appropriate therapy was performed depending on the CT findings. Outcome was classified according to the Glasgow outcome scale (GOS). RESULTS: Overall mortality was 75%. In 15% outcome was unfavourable (GOS 2 and 3), and in 10% favourable (GOS 4, 5) at 24 month follow up. No differences in outcome were found between trauma, stroke, and postelective surgery groups. Unilaterally FDP was associated with a better chance of survival (46% v 13%; p<0.01). Age did not correlate with survival, but younger survivors had a significantly better outcome. Patients in whom an intracranial mass was removed surgically had a 42% survival rate, compared with 8% with conservative treatment (p<0.01). Patients with a shorter delay from FDPs to intervention had a better chance of recovery after trauma and previous intracranial surgery (p<0.05). No patient survived better than a vegetative state, if previous FDPs did not become reactive shortly after therapy. If both pupils became reactive on therapy, the chance of survival was 62%. Of these survivors 42% had a favourable outcome. CONCLUSION: Bilateral restoration of pupillary reactivity shortly after therapy is crucial for survival. Surgical evacuation of an intracranial mass, unilateral FDPs, early intervention, and younger age are related to better chances of survival or recovery. The prognosis of patients with FDPs after trauma, stroke, and previous elective intracranial surgery is similar.